(untitled) (Revista Espinhaço, 2023)
The research had as main aim to present the fossilized pollen types, spores of bryophytes, lycophytes, ferns, algae, insertae sedis and dinoflagellates that were identified in four peatland cores in the Serra do Espinhaço Meridional (SdEM), of Diamantina and São Gonçalo do Rio Preto municipalities, Minas Gerais state, with the earliest age of 35 k cal years BP, to serve as a basis for recognizing the composition of the paleovegetation in the Cerrado area and to assist in the interpretation of vegetational dynamics over time. Images of the microfossils were presented, and information was provided based on a bibliographical survey on the habits (life form) of plants, phytophysiognomies of occurrence and environmental preferences of the possible corresponding taxa today, in order to contribute to paleoecological studies.